2014
DOI: 10.5665/sleep.3840
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effectiveness and Compliance of Positional Therapy with the Sleep Position Trainer in the Treatment of Positional Obstructive Sleep Apnea Syndrome

Abstract: van Maamen JP, de Vries N. Long-term effectiveness and compliance of positional therapy with the Sleep Position Trainer in the treatment of positional obstructive sleep apnea syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 38 publications
5
61
0
2
Order By: Relevance
“…After 6 months, compliance was 64.4%. 22 This type of device, a chest-or neck-worn vibrator, could be a solution for positional OSA as this device might be more comfortable to wear than a device using the tennis ball technique. Compliance with PT using the tennis ball technique could, for example, be limited as a result of the bulkiness of the device resulting in back pain and discomfort, which could lead to disruption of sleep and low sleep quality.…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…After 6 months, compliance was 64.4%. 22 This type of device, a chest-or neck-worn vibrator, could be a solution for positional OSA as this device might be more comfortable to wear than a device using the tennis ball technique. Compliance with PT using the tennis ball technique could, for example, be limited as a result of the bulkiness of the device resulting in back pain and discomfort, which could lead to disruption of sleep and low sleep quality.…”
Section: A B Cmentioning
confidence: 99%
“…1,4 ; Johannes H. van der Hoeven, MD, PhD 5 ; Peter J. Wijkstra, MD, PhD an alarm system, 13 a backpack with ball, 14 behavioral therapy, 15 a pillow with straps, 16 the so-called tennis ball technique, 17,18 a recently developed neck-worn vibrating device, 19,20 and a chestworn vibrating device. 21,22 Oksenberg and Gadoth 23 argue that PT might be a simple solution for patients with mild to moderate positional OSA. While most devices appear effective in the beginning and compliance on a short-term (< 3 months) seems satisfactory, long-term (> 6 months) efficacy is unknown and compliance is poor.…”
mentioning
confidence: 99%
“…Although the contribution of SDB to daytime sleepiness has been questioned in PD, a recent randomized placebo-controlled study in PD patients with SDB demonstrated a significant improvement of both nocturnal sleep consolidation and objective daytime sleepiness in those receiving CPAP treatment [10]. Thus, feasability and efficacy of positional treatment -already a well established alternative to CPAP in patients with positional SDB [11] -need to be evaluated also in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both devices have the capacity to store and register data, such as sleeping posture, that can be uploaded through custom software via a USB connection and personal computer. 6,11,30,34,35 Concerning the neck-worn devices, the device (see Figure 4) described by van Maanen et al 28 consisted of a small vibrating apparatus (30 × 30 × 10 mm, powered by three small batteries). The position sensor provides a vibrating stimulus with a delay of 10 seconds after the supine position is detected, causing the device to vibrate with gradual incremental strength until a different sleeping position is detected, in which case the vibrations ceased immediately.…”
Section: Control Tbtmentioning
confidence: 99%